Exploring Problems and Solutions in estimating Testing Effort for Non Functional Requirement. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Importance of testing has been realized in literature now, although late, but has been realized. Testing of Non Functional Requirement still remains unattended by the Software engineering Community. It is still being given second hand treatment from its specification, design to Testing. We try to analyze the contributory factors of testability of NFR, so that some metrification for the purpose of Effort Estimation due to NFR can be estimated. For the purpose of same we have tried to identify certain, difficulty related to NFR and indicators of its testability.